What determines Rural Financial Illiteracy? An analysis of the relationship with socioeconomic and demographic factors - Reis, Maria Vanessa Silva dos (2024)
The recognition of financial literacy as a growing global policy priority highlights the urgency of addressing financial illiteracy, especially in rural areas of developing countries. This study focuses on the rural area of the Municipality of Capistrano-CE, notable for having one of the most significant rural populations in the Maciço de Baturité-CE region. The objective of this study is to examine the relationship between the level of financial literacy (behavior, attitude and knowledge) with socioeconomic and demographic variables from the perspective of rurality, in addition to encouraging similar research in other rural areas of Brazil. Authors such as Huston (2010); Remund (2010); Jobin and Losekann (2015); Potrich (2016); Pontara (2019) and OECD (2020) offer the theoretical-conceptual and empirical basis of this study. Data collection was carried out through direct field research, where 175 questionnaires were administered in the municipality under analysis. The results indicate that the population surveyed has a low level of financial literacy and is aged between 42 and 80 years, with the majority being female, corroborating the hypothesis that is constant internationally. The factors most closely related to financial illiteracy are: occupation, having dependents, own and parental education, and own and family income. Such results highlight the need for initiatives that economically empower rural communities and reduce vulnerability to financial manipulation and misinformation.